Clash of the generations : managing the new workplace reality - Grubb, Valerie M. (Hoboken : Wiley, 2016)
'Case studies and strategies for more effective multi-generational management Clash of the Generations explores this new and increasingly common workplace phenomenon, and provides strategies to help managers navigate this ever more complex maze. Traditionally, older workers would retire and make room for the next generation; instead, Baby Boomers are now prolonging their time in the workplace, yet the successive generations are still coming in. Senior leaders are now left to manage a blended workplace comprised of up to four generations--each with their own ideas of work ethic, work/life balance, long-term career goals, and much more. Management is challenging at the best of times, but the new prevalence of generation gaps--sometimes even layered--add an entirely new dimension to an already complex responsibility. This book presents case studies and interviews with representatives of companies with age-diverse workforces, detailing innovative strategies for smoothing out the bumps and helping everyone work together. Managers have long wished that their positions came with an instruction manual, and this book delivers with a host of effective inter-generational management strategies illustrated by real-world companies. Manage the multi-generation workplace more effectively Navigate the generational culture clash Adopt proven strategies for helping everyone get along Promote a more positive culture amidst clashing expectations Every generation in the workplace has value, each has their own strengths, their own weaknesses, and their own unique talents. Each is indispensable, and when they come together as a synergistic force, they can be unstoppable. Effective management means bringing out the best in your workforce, and the strategies presented in Clash of the Generations help you streamline your varied workforce into a team more valuable than the sum of its parts'--
'Clash of the Generations details proven strategies that managers and senior leaders can employ to ensure that everyone gets along in the sandbox'--
Baby BoomersGeneration X; Millennials; Generation Z; Using Career Development for Succession Planning at All Levels; To Train or Not to Train; Tying Succession Planning to Career Development; Five Easy Steps to Creating a Career Plan; Step 1: Start with Company Goals; Step 2: Involve Your Employees; Step 3: Decide What Competencies Are Missing; Step 4: Create an Action Plan; Step 5: Monitor, Measure, and Make Adjustments as Needed; Creating a Company-Wide Development Program Specific to Leadership; Determining What Matters; Identifying Candidates; Assessing Current Leadership Skills
Includes bibliographical references and index.
Print version record.
Keywords: BUSINESS & ECONOMICS / Human Resources & Personnel Management; Diversity in the workplace -- Management; Conflict of generations in the workplace -- Management; Intergenerational relations; Older people -- Employment; Youth -- Employment; Electronic books